FLANGE CONNECTIONS OF METAL STRUCTURES - Alexander Surenovich Marutyan; Pavel Sergeevich Chernov (Современная наука и инновации, 2022)
The article presents new technical solutions of flanges, rational scope of which is linear, flat and spatial modification of metallic structures. Practical method of calculation of them is confirmed by the test samples results of a control series of studies.